Tracing the career paths of top-level women football coaches: turning points to understand and develop sport coaching careers - Barker-Ruchti, N.; Lindgren, E.-C.; Hofmann, A.; Sinning, S.; Shelton, C. (Sports Coaching Review, 2015)
This study examines how women football coaches reach top-level coaching positions. Semi-structured interviews and a biographical mapping grid gave a sample of 19 women coaches the opportunity to identify factors that impacted their coaching career paths. Hodkinson and Sparkes' (1997) sociological theory `careership`, and in particular their metaphor of `turning points` are employed to: (1) differentiate between the life events that shaped the women's coaching career development; and (2) outline and conceptualize the career decisions and types of learning that followed these events. The results demonstrate that the women coaches did not necessarily consider coaching as a possible career pathway before and when entering the occupation, but that `structural` turning points enabled them to start and progress a coaching career. Further, `forced` and `self-initiated` turning points significantly affected career development. A key implication is for women coaches to develop `coaching career visions`, which can be created and reinforced through strategic entry points and associated support systems.